An Inverse Transient Nonmetallic Pipeline Leakage Diagnosis Method Based on Markov Quantitative Judgment - Yongmei Hao; Yifei Ma; Juncheng Jiang; Zhixiang Xing; Lei Ni; Jian Yang (Advances in Materials Science and Engineering)
Aiming at the problems of early leakage monitoring of urban nonmetallic pipelines and the large positioning error, an inverse transient urban nonmetallic gas pipelines leakage location method based on Markov quantitative judgment was proposed. A Markov flow state transition probability matrix was established based on the flow data under different pressures obtained by experiments to quantitatively determine the pipeline leakage status. On this basis, an inverse transient leakage control equation suitable for urban nonmetallic gas pipeline leakage location was constructed according to the actual. The difference between the pressure and the calculated pressure was sought for the objective function. Finally, the objective function was optimized in conjunction with the sequential quadratic programming (SQP) method to obtain the actual leakage parameters and calculate the size and location of the leakage source. The results show that the inverse transient leakage localization method based on Markov’s quantitative judgment can more accurately determine the leakage status of the pipeline and calculate the early leakage parameters and leakage location of the gas pipeline, which improves the positioning accuracy.